(untitled) (Research, Society and Development, 2020)
Objective: To verify the prevalence of infections related to health care in adult patients seen in Intensive Care Units. Methodology: Descriptive, epidemiological, retrospective study with a quantitative approach on the occurrence of HAI in the adult intensive care unit, in a hospital in the Armed Forces of Belém, State of Pará. Result: 91 patients were selected, the majority of whom were elderly, from both genders and from clinical / surgical hospitalization. As for the profile of infections, there was a predominance of those related to the respiratory system with (73.6%), followed by the urinary tract with (17.6%) and bloodstream with (3.3%). Among the microorganisms identified there is a predominance of Acinetobacter baumanni (28.6%) and Candida SP (28.6%). The most used antimicrobials were: Ceftriaxone (35.5%), Tazocin (32.3%) and Vancomycin (29.0%). Conclusion: It is considered to have reached its goal regarding the prevalence of HAIs in the ICU of the researched institution, enabling the health team to list prevention strategies and measures with greater specificity and targeting the local reality. This study contributed to the knowledge about the data on the prevalence of HAIs in the hospital environment, making evident the need for greater epidemiological surveillance of infections in the Intensive Care Unit.